Digital Storytelling Animation Media with Minimum Competency Assessment to Enhancing Students Folktales Reading Comprehension - Faizah, Auliya Nurul; Purwati, Panca Dewi; Murtini, Tri (Universitas Pendidikan Ganesha, 2024)
This research is motivated by observational data indicating the low learning outcomes of second-grade students in the competency of reading to folktales, which is attributed to the limited use of media in teaching. Therefore, this research aims to developed an instructional tool: digital animation storytelling media with Minimum Competency Assessment (MCA). The research method employed in this study was Research and Development (R&D), utilizing the ADDIE model. This study involved a class teacher and 26 learners in grade II of an Elementary School. The primary objective of this research was to analyze the feasibility and effectiveness of the digital animation storytelling media with MCA for the second-grade class in enhancing the competency of reading to folktales. Data were collected using a questionnaire to assess media feasibility and pretest-posttest questionnaires to measure the media's effectiveness. The results of the media feasibility assessment, based on the questionnaire, obtained a percentage of 90%, indicating